2006
DOI: 10.1124/dmd.105.009134
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Metabolism of Endosulfan by Human Liver Microsomes and Human Cytochrome P450 Isoforms

Abstract: ABSTRACT:Endosulfan (6,7,8,9,10,10-hexachloro-1,5,5a,6,9,9a-hexahydro-6,9-methano-2,3,4-benzo(e)dioxathiepin-3-oxide) is a broad-spectrum chlorinated cyclodiene insecticide. This study was performed to elucidate the stereoselective metabolism of endosulfan in human liver microsomes and to characterize the cytochrome P450 (P450) enzymes that are involved in the metabolism of endosulfan. Human liver microsomal incubation of endosulfan in the presence of NADPH resulted in the formation of the toxic metabolite, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 29 publications
0
47
1
1
Order By: Relevance
“…It is classified as a "possible human carcinogen" based on thyroid tumors in rat. ToxCast true actives for CYPs (ES: hCYP2B6 & hCYP3A4; FP: hCYP2C9) correlated well with in vivo toxicity [7,8]. Other true activities for ES and FP were for generalized liver enzyme activity, which could be predictive of liver toxicity observed in vivo.…”
Section: Discussion/conclusionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is classified as a "possible human carcinogen" based on thyroid tumors in rat. ToxCast true actives for CYPs (ES: hCYP2B6 & hCYP3A4; FP: hCYP2C9) correlated well with in vivo toxicity [7,8]. Other true activities for ES and FP were for generalized liver enzyme activity, which could be predictive of liver toxicity observed in vivo.…”
Section: Discussion/conclusionmentioning
confidence: 90%
“…Their action in the brain is very complex due to biotransformation to toxic metabolites that can act on GABA A R (e.g., FP sulfone [6]). Each is detoxified by P450s (CYP2B6, CYP3A4-5: ES; hCYP2C9: FP) [7,8] [9]. These well characterized in vivo effects provide a basis for comparing toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, after the current communication had been prepared for submission, a manuscript was submitted and published from another laboratory (Lee et al, 2006). Lee et al (2006) reported on the metabolism of ␣-and ␤-endosulfan isomers, whereas the present study only reports on the metabolism of the ␣-isomer.…”
mentioning
confidence: 99%
“…Subsequently, after the current communication had been prepared for submission, a manuscript was submitted and published from another laboratory (Lee et al, 2006). Lee et al (2006) reported on the metabolism of ␣-and ␤-endosulfan isomers, whereas the present study only reports on the metabolism of the ␣-isomer. Although the results from the two laboratories on metabolism of endosulfan-␣ are in general agreement, the current communication extends the findings in the development of endosulfan-␣ as a simultaneous probe for CYP2B6 and 3A4 in human liver microsomes.…”
mentioning
confidence: 99%
“…The inhibitory effects of known P450 isoform-selective inhibitors on the formation of N-desbenzylbenidipine and dehydrobenidipine were evaluated to determine the P450 isoform(s) involved in the metabolic pathway. The formation ratio of N-desbenzylbenidipine and dehydrobenidipine from benidipine racemate or enantiomers was determined from the reaction mixtures incubated in the presence or absence of known P450 isoform-selective inhibitors (Kim et al, 2006;Lee et al, 2006). The P450 isoform-selective inhibitors used were furafylline (10 M) for CYP1A2, coumarin (100 M) for CYP2A6, triethylenethiophosphoramide (5 M) for CYP2B6, montelukast (0.1 M) for CYP2C8, sulfaphenazole (10 M) for CYP2C9, S-benzylnirvanol (1 M) for CYP2C19, quinidine (10 M) for CYP2D6, diethyldithiocarbamate (10 M) for CYP2E1, ketoconazole (1 M) for CYP3A, and azamulin (5 M) for CYP3A.…”
mentioning
confidence: 99%